The Apple TV pocket guide - Carlson, Jeff (Peachpit Press, 2007)
The new Apple TV is an easy to use and fun way to wirelessly play all your favorite iTunes content from your Mac or PC on your widescreen TV, including movies, TV shows, music, photos, and podcasts. Using Apple TV's stunning new interface, anyone can quickly browse and view their entire collection of digital media from across the room using the simple and intuitive Apple Remote. Apple TV features a 40GB hard drive for holding up to 50 hours of video. It easily connects to almost all modern widescreen televisions, and is slated to ship in February 2007 for $299. New Apple TV users will want to start using their devices as soon as they get their hands on them, and this guide shows them how. The Apple TV Pocket Guide reveals the secrets to using Apple's latest popular invention. This handy guide offers the quickest way to learn the Apple TV features, from syncing your iTunes movie and photo collection wirelessly to Apple TV to connecting Apple TV to your widescreen TV to playing your movies and showing your photos directly on your TV! Readers will also find thorough coverage of using the handy Apple remote. Along the way, the author offers hints for making the most of Apple TV and troubleshooting advice for when the gadget become uncooperative.